Sol-Gel finishing for protective fabrics - Nurul Hidayah, Abu Bakar; Hartina, Mohd Yusop; Wan Norfazilah, Wan Ismail; Noreen Farzuhana, Zulkifli (Biointerface Research, 2022)
Sol-gel method has been used since the early 1960s in various applications. There has been a growing interest in this method in recent decades, its materials, and its functionality. The sol-gel reaction consists of a series of simple hydrolysis and condensation reactions, and they are easy to perform and do not require special conditions or high temperatures. This reaction can be influenced by several factors: water-to-precursor molar ratio, types of catalyst, pH, modifier, reaction, aging temperature, and varying solvent. Scientific databases, namely Scopus and ScienceDirect, mainly address the organic solvent-based sol-gel method. Since 1996, the water-based sol-gel method has attracted much attention to simplify the procedure further and reduce cost and environmental damages. This is a review of water-based and typical solvent-based sol-gel methods, focusing on protective fabric coatings. It discusses the most relevant and recent findings related to the sol-gel method, including its applications, advantages and limitation, and future potential. It describes the effects of using water to replace organic solvents that can influence the characteristics and properties of sol-gel materials. Water-based sol-gel preparation methods are relatively advanced, and some products are currently on the market. However, many difficulties related to their water-precursor compatibility prevail. Therefore, chemistry and physics are areas that need to be exploited to create new materials that meet the protective fabric criteria.